Sociology of Student Discipline in Madrasahs: A Study of the Relationship between Guidance and Counseling Teachers, Learning Motivation, and Social Control - Verlin Aryanti; Muh. Hanif (Penerbit Presisi Pustaka, 2026)
This research explores the sociological connection between students and Guidance and Counseling (BK) educators at Madrasah Tsanawiyah (MTs), focusing on student discipline, learning motivation, adherence to school regulations, and opportunities for social mobility. The study aims to investigate how BK educators can act as agents of social control in shaping students' character and behavior within the school environment. Using interviews, observations and documentation are data collection techniques used in a qualitative descriptive approach. We conducted the study with BK teachers, students, homeroom teachers, parents and alumni. Findings indicate that discipline development practices are implemented from the very onset of students' admission to the school. This is done through the implementation of school regulations, continuous supervision, weekly evaluations, counseling methods, and collaboration with parents. In this context, BK educators have a dual role: they act not only as a counselor but also as an intermediary between institutional values and students social behavior. The other piece of it is that different students respond better to different disciplinary practices. Some accept them and try to improve themselves, while others resist and repeatedly violate the rules. The study also shows that consistent rule enforcement contributes positively to students' learning motivation, sense of responsibility, and educational aspirations. This indirectly opens up opportunities for students to improve their social status in the future. However, BK educators face challenges in balancing their authority with emotional closeness to students, as they are sometimes viewed negatively by students. Therefore, effective communication, empathetic counseling, and a supportive school climate are essential in strengthening the sociological relationship between BK educators and students in Islamic educational institutions.